Aspects of improving metrological characteristics of a sensor based on palladium nanoparticles for methionine determination - Eduard V. Gorchakov; Darya O. Perevezentseva; Elena A. Vaitulevich; Oksana V. Dubinina (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The need to accurately determine the concentration of methionine in various biogeochemical samples. This amino acid serves as a precursor for the biosynthesis of proteins and peptides, as well as a donor of methyl groups, making it an essential participant in numerous biochemical processes, including cysteine synthesis. Additionally, methionine can be found in certain proteins, such as casein. Methionine is a widely used pharmacological drug that has a lipotropic effect and a positive impact on liver function. It enhances the synthesis of phospholipids, choline, and lecithin, as well as having an antidepressant effect due to its s-adenosylmethionine content. It is also a radioprotector and can be used in cancer diagnosis. Methionine is commonly used as an amino acid supplement in poultry and cattle feed, as well as in sports nutrition and medicine. Aim. To investigate the dependence of the metrological characteristics of electrochemical sensors for methionine on the morphological properties of palladium nanoparticles and the composition of the low-molecular reducing agents used for their synthesis. Methods. Transmission electron microscopy, cyclic voltammetry. Results and conclusions. The paper considers the effect of the reducing agent nature on the morphological characteristics of palladium nanoparticles and the composition of their micelles. Sodium borohydride, sodium citrate, and a mixture of borohydride and sodium citrate were used as reducing agents. All the synthesized nanoparticles have a cubic face-centered crystal cell. The composition of the micelles depends on the reducing properties of the reagents used. The reasons for the improved metrological characteristics of methionine determination on an electrochemical sensor based on palladium nanoparticles obtained using sodium citrate are associated with the growth of a shell on the nanoparticle core material, forming a heterostructure.